Pengembangan Kapasitas Karyawan UMKM Melalui Pemasaran Berbasis Komunitas dan Pengaruhnya Terhadap Keunggulan Bersaing - Amrullah, Asriyani; Nurhikmah, Andi Reski; Muhrami, Siti Nardiyah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the development of MSME employees’ capacity through community-based marketing and its influence on competitive advantage in the digital era. As the backbone of Indonesia’s economy, MSMEs face challenges in human resource quality, particularly in digital literacy and marketing skills. Adopting a descriptive qualitative approach, this research was conducted among MSMEs in Makassar City that actively use social media to engage with customer communities. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed thematically using NVivo software. The findings demonstrate that enhancing employees’ skills in digital literacy, communication, and community data analysis significantly contributes to customer loyalty, product innovation, as well as brand differentiation and identity. Community-based marketing not only fosters stronger emotional relationships with customers but also improves marketing efficiency through word-of-mouth and accelerates innovation cycles through co-creation practices. These results suggest that MSMEs’ competitive advantage is multidimensional, shaped by the synergy between human resource capacity development, digital community management, and dynamic capabilities in adapting to market changes. Furthermore, this study highlights the role of digital platforms as enablers of sustainable marketing practices, reinforcing MSMEs’ adaptability and resilience in the globalized marketplace. Consequently, the study contributes to digital marketing literature and offers practical recommendations for MSMEs, including continuous employee training, collaborative innovation, and strategic use of social media, to sustain competitiveness in increasingly dynamic and globalized business environments.